COMMUNITY STUDY DIGGER STONE AREA ALONG THE SAND HILLS IN KANAGARIAN AIE DINGIN DISTRICT SOLOK - Susanti, Idra; Erita, Yeni; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information about Community Studies Along the Sandstone Quarry Hills area in Solok Kanagarian Aie Dingin: Tools used excavator sandstone, sandstone quarrying process, incomes sandstone diggers, diggers cause of the persistence of the community as sandstone.Type of research is qualitative. Information in the research is the sandstone diggers. Determining the techniques of information by researchers is the purposive sampling where subjects are taken at the community based informant who worked as an excavator along sandstone hills area in Solok district kanagarian Aie Dingin.Results of research in the field as follows: a) Equipment used in the extracting digger sandstone sandstone: eksafator, snails machines, pipes, filters, hoes, skap, blades, hoses, and conveyance ( wagon ), diesel. b ) The process of quarrying sandstone: Land excavated using eksafator, after which the water is raised up with the aid of a machine to wash new sandstone and later filtered to separate the rock with sand after it had washed away through the pipeline relocation of sand. c ) excavating the sandstone income: monthly income as diggers sandstone around Rp 1500000-2000000 and needs within one month approximately 3,000,000 Rp.1.500.000 - even more than specified . d ) The cause of the survival of the community as a digger sandstone: Due to low education , employment difficulties and just work as a digger sandstone that is before them at the present time